Teargas and Selfie Cams: Foreign Protests and Media in the Digital Age. Issue 2 (24th February 2022) - Green-Riley, Naima; Kruszewska-Eduardo, Dominika; Fu, Ze
Abstract: This study explores the impact of repression of foreign protests and the media source reporting the news upon American foreign policy preferences for democracy promotion abroad. We use two survey experiments featuring carefully edited video treatments to show that even short media clips presenting foreign protests as violently repressed increase American support for targeted sanctions against the hostile regime; however, these treatments alone do not inspire respondents to political action. Furthermore, we do not find evidence that mobile treatment magnifies the effects of violence.